2020
DOI: 10.1177/0284185120933984
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy with bronchial artery embolization and tranexamic acid for hemoptysis

Abstract: Background While most previous studies have viewed tranexamic acid as a bridging or temporary therapy, our preliminary study offers insights into the combined therapy of antifibrinolytic agent with endovascular treatment for hemoptysis. Purpose To investigate the feasibility and safety of combined therapy, to analyze factors affecting the outcomes of combined therapy, and to compare the effectiveness of combined therapy between groups with different etiologies. Material and Methods Between January 2011 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…BACE is an emerging method of local interventional therapy in recent years, in which chemotherapy drugs are directly infused into the supplying vessels of the lesions through catheters, and BACE is able to rise drug concentrations entering the lesions compared with superficial intravenous chemotherapy [10]. It has been reported that local therapeutic efficacy of BACE is 2-6 times that of intravenous chemotherapy [11]. BACE can maximize the therapeutic effect with a relatively small amount of chemotherapeutic drugs [12].…”
Section: Discussionmentioning
confidence: 99%
“…BACE is an emerging method of local interventional therapy in recent years, in which chemotherapy drugs are directly infused into the supplying vessels of the lesions through catheters, and BACE is able to rise drug concentrations entering the lesions compared with superficial intravenous chemotherapy [10]. It has been reported that local therapeutic efficacy of BACE is 2-6 times that of intravenous chemotherapy [11]. BACE can maximize the therapeutic effect with a relatively small amount of chemotherapeutic drugs [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent bleeding after embolization has been reported in 10-55% of cases. This can occur due to imperfect embolization, recanalization of embolized blood vessels, collateral circulation, or the progression of the underlying disease 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding its effectiveness in haemoptysis, it has been studied only in few trials. Typically, TA is administered orally [62] or intravenously [63], yet inhaled [64,65] and endobronchial [66] forms have been recently discussed.…”
Section: Conservative Treatment: Tranexamic Acidmentioning
confidence: 99%
“…Bronchial artery embolization (BAE) is a minimally invasive and efficient technique in managing massive and recurrent haemoptysis as a single therapy or in combination with conservative medication or surgery [13,62]. BAE, first introduced by Remy et al in 1974 [76], is performed in view of lowering the perfusion pressure by occluding the systemic arterial inflow of the culprit vessels [25].…”
Section: Bronchial Artery Embolizationmentioning
confidence: 99%
See 1 more Smart Citation